Come the spring eaudiobook - Garwood, Julie (Clayborne Brides, 2012)
With more than 13 million books in print, Julie Garwood is an exceptionally popular author. Since her first novel was published in 1985, eleven of her works, including this title and The Wedding, have been New York Times best-sellers. Set in the Old West, Come the Spring is part of the Clayborne family saga. Cole Clayborne has reluctantly agreed to serve as a federal marshal only long enough to capture a gang of murderous bank robbers. As he searches to discover who is in cahoots with the outlaws, Cole interrogates three beautiful young women. Although his aim is to arrest the robbers, as he questions her, one gentle doe-eyed woman captures Cole's heart. Filled with all the humor, passion, and excitement that are Julie Garwood's trademark, Come the Spring is a thrilling combination of love and adventure. For this unabridged audio recording, narrator Richard Ferrone brings to life each vivid character, from the keen-eyed lawmen to calico-skirted vixens.